CAD/CAM Complete Denture Systems and Physical Properties: A Review of the Literature. (14th May 2021) - Baba, Nadim Z.; Goodacre, Brian J.; Goodacre, Charles J.; Müller, Frauke; Wagner, Stephen
Abstract: Purpose: CAD/CAM complete dentures have increased in popularity and a wide variety of systems are currently available. These prostheses present many advantages for clinicians, technicians and patients. Subtractive manufacturing is used by most of the available systems while a few manufacturers use an additive manufacturing technique. This article describes the currently available systems and materials available for the fabrication of CAD/CAM complete dentures and reviews the literature relative to their physical properties. Methods: A comprehensive review of the literature was completed to enumerate the currently available techniques to fabricate CAD/CAM complete dentures and discuss their physical properties. A search of English language peer‐reviewed literature was undertaken using MEDLINE and PubMed on research articles published between 2000 and 2019. A hand search of relevant dental journals was also completed. Results: The literature indicates the physical properties of CAD/CAM milled poly(methylmethacrylate) or PMMA as it is commonly described is superior to conventionally processed PMMA for the fabrication of complete dentures. Conclusion: The incorporation of CAD/CAM technology into complete denture design and fabrication streamlines the clinical and laboratory processes and provides improved physical properties that enhance denture quality.